Profesionalisme Pemimpin Milenial Berkarakter Bela Negara Era 4.0 di Yes Institute Indonesia - Roudlotul Badi'ah; Rizna Ramadhani Winanda; Hilda Khuzaifah (Universitas Batanghari Jambi, 2022)
Industrial revolution 4.0 requires company leaders to continue to innovate to compete. The leader of YES Institute Indonesia is currently facing new, bigger competition and better technology. Therefore, this study aims to determine the professionalism of millennial leaders with the character of State Defense in meeting the opportunities and challenges of the 4.0 industrial revolution era to produce a young generation who excel at YES Institute Indonesia. The research method used is descriptive qualitative, through interviews with the Founder of YES Institute Indonesia, documentation, and literature. Data analysis using Interactive Model analysis with the help of ATLAS.ti software 9. The results show the opportunities faced by millennial leaders in the era of the industrial revolution 4.0, namely utilizing technology through social media and websites to promote service products and educate the market, exchange ideas, increase knowledge and information, facilitate communication and discussion. While the challenges from yourself are caused by the closest people, limited team members, marketing professionals, new competitors, consistency. The challenge of innovation design is to add online services, develop websites and applications. The challenge is being able to upgrade yourself and accept change by utilizing social media and forming alumni groups to exchange ideas from different generations.